Principles of compilers a new approach to compilers including the algebraic method - Su, Yunlin (Springer, 2011)
Principles of Compilers: A New Approach to Compilers Including the Algebraic Method introduces the ideas of the compilation from the natural intelligence of human beings by comparing similarities and differences between the compilations of natural languages and programming languages. The notation is created to list the source language, target languages, and compiler language, vividly illustrating the multilevel procedure of the compilation in the process. The book thoroughly explains the LL(1) and LR(1) parsing methods to help readers to understand the how and why. It not only covers established methods used in the development of compilers, but also introduces an increasingly important alternative the algebraic formal method. This book is intended for undergraduates, graduates and researchers in computer science.